Impacts of climate and land use/cover change on mini-hydropower generation in River Kyambura watershed in South Western part of Uganda - Musa Aruho Tusingwiire; Martin D. Tumutungire; Jotham Ivan Sempewo; Swaib Semiyaga (Water Practice and Technology, 2023)
This study explored the combined impacts of climate and land-use change on mini-hydropower generation in the Kyambura watershed. The soil and water assessment tool (SWAT) was used as a hydrological model whereas the statistical downscaling model (SDSM) was used to downscale meteorological data for the Kyambura watershed for the year 2050. The results show that there will be an increase in urban land by 11.89%, barren land by 25.78%, water by 0.49% and a reduction in percentage area coverage of vegetation by 38.17% by the year 2050. A 10.6 and 17.7% increase is anticipated in average annual hydropower generated by the year 2050. There is, therefore, a need to develop governing policies to regulate management practices to preserve the integrity of the watersheds and ensure the reliability of power production. HIGHLIGHTS Quantifies LULC changes within the Kyambura catchment from 1989 to 2019.; Predicts and quantifies LULC changes within the Kyambura catchment by the year 2050.; Predicts the changes in climate, stream flows and Hydropower generation within the Kyambura catchment by the year 2050.; Elucidates on the impacts of climate and Land use/cover change on mini-hydropower generation.;